How to Design, Implement, and Analyse a Survey - Arundel, Anthony (How to Research Guides, 2023)
This insightful book examines all aspects of the design process and implementation of questionnaire surveys on the activities of business, public sector, and non-profit organizations. Anthony Arundel discusses how different aspects of the survey method and planned statistical analysis can constrain question design, and how these issues can be effectively resolved.